Seeing others suffer and enjoying it? The Model of Individual and Social Appraisals of Misfortunes of others in media reception - Suter, Lilian; Döveling, Katrin (Frontiers in Psychology, 2024)
Suffering and misfortunes of other people are often portrayed in the media. Recipients react to these portrayals with different emotions. This article elucidates and clarifies schadenfreude (pleasure at the misfortune of others) and sympathy (feeling concern or sorrow over another person's distress) in media experiences. A thorough literature review provides in-depth insights into the formation of affective dispositions and schadenfreude from various psychological perspectives. This conceptual analysis leads to the "Model of Individual and Social Appraisals of the Misfortune of Others" (MISAM) which first reveals the determining intrapersonal factors within the emotional experience of schadenfreude and sympathy. Second, it discloses the social component vital for understanding the construction and regulation of these emotions. The model combines individual and social appraisal processes and identifies the factors involved in the elicitation and regulation of schadenfreude and sympathy in the media reception of misfortunes. With the aim of integrating different perspectives, we incorporated Affective Disposition Theory and recent work from social psychology and used an appraisal framework. The MISAM opens the path for further investigation of schadenfreude and sympathy in media reception, beyond entertainment experiences.